2014
DOI: 10.15517/rbt.v62i4.13057
|View full text |Cite
|
Sign up to set email alerts
|

The effect of astaxanthin on resistance of juvenile prawns Macrobrachium nipponense (Decapoda: Palaemonidae) to physical and chemical stress

Abstract: Abstract:In recent years, the use of new scientific techniques has effectively improved aquaculture production processes. Astaxanthin has various properties in aquaculture and its antioxidant benefits have been closely related to stress resistance; besides, it is an essential factor for growth in many crustaceans and fish. The objective of this study was to evaluate the resistance of prawn (Macrobrachium nipponense) fed diets containing different amounts of astaxanthin (AX) to the shock and stress of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…); (ii) as for oriental river prawn Macrobrachium nipponense , endurance to multiple chemical and physical stresses such as deprived oxygen supply (0.5 mg L −1 ), ammonia spike (0.75 mg L −1 ) and thermal shock (0°C) was effectively ameliorated in prawns accepting diets containing different amounts of astaxanthin (50–150 mg kg −1 diet) after 10 weeks (Tizkar et al . ).…”
Section: Uses and Benefits Of Astaxanthinmentioning
confidence: 97%
See 1 more Smart Citation
“…); (ii) as for oriental river prawn Macrobrachium nipponense , endurance to multiple chemical and physical stresses such as deprived oxygen supply (0.5 mg L −1 ), ammonia spike (0.75 mg L −1 ) and thermal shock (0°C) was effectively ameliorated in prawns accepting diets containing different amounts of astaxanthin (50–150 mg kg −1 diet) after 10 weeks (Tizkar et al . ).…”
Section: Uses and Benefits Of Astaxanthinmentioning
confidence: 97%
“…On the other hand, the administration of 50 and 100 mg astaxanthin kg À1 diet from either algal or synthetic sources resulted in enhanced tolerance of juvenile Kuruma prawn P. japonicus to hypoxic conditions (<0.5 mg L À1 ) in a trial lasted for 9 weeks (Chien & Shiau 2005). Two separate studies have reported better stress tolerance and disease resistance of freshwater prawns: (i) in the case of giant freshwater prawn M. rosenbergii, systemic astaxanthin injection at either dose of 0.67 or 1.34 nmol g À1 through ventral sinus of the cephalothorax has attributed a profound increment in total haemocyte count (THC) and hepatic astaxanthin content leading to improved resistance against Lactococcus garvieae infection, although no direct stress test was performed (Angeles et al 2009); (ii) as for oriental river prawn Macrobrachium nipponense, endurance to multiple chemical and physical stresses such as deprived oxygen supply (0.5 mg L À1 ), ammonia spike (0.75 mg L À1 ) and thermal shock (0°C) was effectively ameliorated in prawns accepting diets containing different amounts of astaxanthin (50-150 mg kg À1 diet) after 10 weeks (Tizkar et al 2014). Approaches taken to examine the effect of astaxanthin on fish resulted in the same beneficial physiological effects.…”
Section: Stress Tolerance and Disease Resistancementioning
confidence: 99%
“…AST has very low solubility in water and it is slightly soluble in organic reagents, such as acetone (0.20 mg/mL), DMSO (0.5 mg/mL), chloroform (10 mg/mL), and dichloromethane (30 mg/mL) [ 17 ]. It has been reported that the antioxidant activity of AST is ten times higher than that of beta-carotene and one hundred times higher than that of α-tocopherol [ 19 ]. Moreover, it has been noted that this pigment has the potential to prevent and treat several health problems, such as inflammation, hepatic dysfunction, diabetes, cardiovascular and neurodegenerative diseases, cancers, gastrointestinal disorders, and ocular problems, as well as to improve fertility [ 20 ], skin and muscle conditions [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Astaxanthin is widely found in nature, especially in aquaculture products such as shrimp, crab, and fish [ 18 ]. Astaxanthin, as a red–orange ketocarotenoid, has excellent antioxidant activity [ 19 ] and it is widely used as a color additive in production [ 20 ]. Lac dyes are pink–red–purple organic colourants derived from an insect and contain several components, such as laccaic acid A, laccaic acid B, laccaic acid C, laccaic acid D, and laccaic acid E [ 21 ].…”
Section: Resultsmentioning
confidence: 99%